Are Multimorbidity Patterns Associated with Mobility Limitations in Community-Dwelling Brazilian Older Adults? - Rosa, Rafaela Aguiar; Martins Cândido, Letícia; Carelli Pereira de Avelar, Núbia; Danielewicz, Ana Lúcia (Physical & Occupational Therapy in Geriatrics, 2025)
Background: Understanding how different patterns of chronic diseases relate to mobility limitations in older adults is crucial for more effective actions to prevent chronic diseases. This study aimed to verify the association between multimorbidity patterns and mobility limitation in community-dwelling older adults in southern Brazil. Methods: A cross-sectional study with an analysis of 308 older adults. Four multimorbidity patterns were analyzed: (1) cardiopulmonary; (2) vascular-metabolic; (3) musculoskeletal; and (4) coexisting patterns. Mobility limitation was considered when the older adults performed the Timed Get Up and Go test in ≥10 s. Logistic regression analyses were performed, adjusted for sociodemographic and behavioral variables. Results: Older adults with the vascular-metabolic pattern had 2.17 times higher odds (95% CI: 1.05–4.45) of mobility limitation. Those with the cardiopulmonary pattern had nearly seven times greater odds (OR: 6.84; 95% CI: 1.76–26.5), while individuals with coexisting patterns had almost five times higher odds (OR: 4.53; 95% CI: 1.78–11.5) compared to those without the same patterns. No statistically significant association was observed with the outcome analyzed for the musculoskeletal pattern. Discussion: The older adults affected by cardiopulmonary, vascular-metabolic and coexisting patterns were more likely to present mobility limitations.